Breast cancer - Marques, Laura (2003)
Breast cancer continues today to be an important public health problem internationally and nationally for the problem of their approach continues to have an interest. The understanding of carcinogenesis and risk factors in this type of cancer to facilitate intervention in primary and secondary prevention. In secondary prevention is no consensus on the type of screening to be carried out to women over 50 years old. The same is not true in relation to the age group 40-49 years of age, where there is no uniformity of action, suggesting in this case that each woman should decide for herself what kind of screening you want to be submitted, with based on their clinical history and how appreciates the risks and benefits. It ends with a proposal for intervention in the light of scientific knowledge to the family doctor for the prevention and early diagnosis of breast cancer.